2020
DOI: 10.1016/j.jdsr.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways promoting epithelial mesenchymal transition in oral submucous fibrosis and oral squamous cell carcinoma

Abstract: Summary Epithelial-mesenchymal transition (EMT) is a critical process that occurs during the embryonic development, wound healing, organ fibrosis and the onset of malignancy. Emerging evidence suggests that the EMT is involved in the invasion and metastasis of cancers. The inflammatory reaction antecedent to fibrosis in the onset of oral submucous fibrosis (OSF) and the role of EMT in its malignant transformation indicates a hitherto unexplored involvement of EMT. This review focuses on the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 159 publications
(176 reference statements)
0
31
0
Order By: Relevance
“…Likewise, chrysophanol also inhibited SAS cell invasion ability (Figure 3), but it was reversed by IL-6 and IL-8 treatment (Figure 3A,B), further confirming that the effects were IL-6-and IL-8-dependent. Previous studies have reported that regulation of oral cancer metastasis involves many signaling pathways, such as MAPK, PI3K/AKT, and FAK/Src [51,52]. Recently, IL-6 has been shown to stimulate migration of oral cancer cells via the phosphorylation of STAT3 [45].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, chrysophanol also inhibited SAS cell invasion ability (Figure 3), but it was reversed by IL-6 and IL-8 treatment (Figure 3A,B), further confirming that the effects were IL-6-and IL-8-dependent. Previous studies have reported that regulation of oral cancer metastasis involves many signaling pathways, such as MAPK, PI3K/AKT, and FAK/Src [51,52]. Recently, IL-6 has been shown to stimulate migration of oral cancer cells via the phosphorylation of STAT3 [45].…”
Section: Discussionmentioning
confidence: 99%
“… 36 EMT markers, which are mediators of EMT regulated complex signalling pathways have detrimental role in the pathogenesis of OSF and OSCC. 37 IGF‐I/IGF‐IR signalling is associated EMT progression in various type of cancers. 38 Our data indicated that OSF remarkably increased the cell‐matrix adhesion, invasion and migration abilities and the activity of MMP‐2 of oral cancer and affected the EMT by enhancing the expression of N‐cadherin, fibronectin and vimentin and downregulating the expression of E‐cadherin in human oral cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…As disease progressed, the fibers increased in thickness and involved the deeper submucosal region[ 35 ] and collagen III and IV are replaced with Type I. [ 36 ]…”
Section: Discussionmentioning
confidence: 99%